2012
DOI: 10.1002/ange.201204349
|View full text |Cite
|
Sign up to set email alerts
|

Metal Carbonyl–Gold Nanoparticle Conjugates for Live‐Cell SERS Imaging

Abstract: The field of bioorganometallic chemistry, the junction of organometallic chemistry and biology, is coming of age. In particular, applications of metal carbonyl compounds in biological immunoassays (metallo-immunoassays), pharmaceuticals, CO therapy (CO-releasing molecules), and bioimaging have emerged. [1][2][3][4] One of the useful characteristics of metal carbonyl compounds is the strong CO stretching vibrations in the mid-IR region (1800-2200 cm À1 ); a region that is relatively free of interference from ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 56 publications
0
13
0
1
Order By: Relevance
“…[9] Gold nanoparticles (AuNPs) covered by Raman reporters have been used for SERS to detect cancer cells in vitro and tumours in vivo. [10][11][12][13] Raman reporters combined with AuNPs produce an optical contrast to distinguish between cancer and normal cells and their conjugation with antibodies allowed them to determine the expression of relevant biomarkers in molecular imaging. [13] Qian et al reported that, when conjugated to tumour targeting ligands, these SERS-NPs were able to target tumour markers…”
Section: Introductionmentioning
confidence: 99%
“…[9] Gold nanoparticles (AuNPs) covered by Raman reporters have been used for SERS to detect cancer cells in vitro and tumours in vivo. [10][11][12][13] Raman reporters combined with AuNPs produce an optical contrast to distinguish between cancer and normal cells and their conjugation with antibodies allowed them to determine the expression of relevant biomarkers in molecular imaging. [13] Qian et al reported that, when conjugated to tumour targeting ligands, these SERS-NPs were able to target tumour markers…”
Section: Introductionmentioning
confidence: 99%
“…Anti-HER2 2-(4-(bis(4-(diethylamino)phenyl) (hydroxy)methyl)phenoxy)ethyl 5-(1,2-dithiolan-3-yl)pentane [39] 60-nm gold nanosphere BSA Anti-HER2 CyNAMLA-381 [29] SKBR3; breast and OSCC; head-andneck squamous cell carcinoma 60-nm gold nanosphere PEG Anti-HER2 and anti-EGFR B2LA, Cy3LA [40] OSCC; oral squamous 60-nm gold nanosphere PEG Anti-EGFR Organometallic osmium carbonyl cluster [41] MDA-MB-231; breast 40-nm gold nanosphere Silica Anti-CD24 and -CD44 MGITC [42] Tu686; head-andneck squamous cell carcinoma CHO; ovarian 35-50-nm silver nanoparticles NA Anti-EGF 2,4-dinitrobenzoic acid [43] Gold nanoparticlebased microfluidic chip NA NA 4-mercaptobenzoic acid [44] HEK293; human embryonic kidney 13-nm gold nanosphere…”
Section: Thiolated Peg and Dtbementioning
confidence: 99%
“…The synthesized probe produced T2 weighted contrast and was simultaneously used as a SERS active material both in silico and in vivo. Kong et al 164 prepared metal carbonyl based biotags by combining osmium carbonyl clusters and AuNPs, as an example of an organometallic-AuNPs (OMAuNPs) conjugate used to cell SERS imaging. 164 It showed clearly the advantage of transition-metal carbonyl compounds, for which the CO stretching vibration signal was well separated from other molecular vibrational modes of the cells in live-cell imaging.…”
Section: Figurementioning
confidence: 99%